Migrant Workers and the Trans-Pacific Partnership: A Regulatory Impact Analysis of the TPP's Temporary Entry Provisions - Mertins-Kirkwood, Hadrian (Trade and Investment Research Project, 2016)
This study investigates the TPP's chapter on "temporary entry for business persons" to understand its potential consequences for Canadian immigration policy and the Canadian labour market. It examines the general provisions that apply to all TPP countries as well as Canada's specific commitments for different categories of workers under the TPP. The study finds that the TPP will give more leeway to employers to hire migrant workers and transfer employees across borders—even in industries and regions where unemployment is high and domestic workers are available—without offering mobility rights to workers themselves. Although the short-term impact on the Canadian labour market will likely be small, the potential long-term impact of the TPP's temporary entry provisions is significant. Like other aspects of the TPP, these provisions override Canada's existing immigration policy and cannot be changed by a future government.
Keywords: Deep integration; Employment; International trade; Investment policy; Labour